2022
DOI: 10.3389/fmed.2022.975229
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bridge-in, objective, pre-assessment, participatory learning, post-assessment, and summary teaching strategy in Chinese medical education: A systematic review and meta-analysis

Abstract: The BOPPPS teaching strategy has been used recently in many medical courses as an improved and more practical pedagogy in China. Nevertheless, the effectiveness of this pedagogy has not been fully assessed in terms of knowledge and skill outcomes in medical education. This meta-analysis aimed to evaluate the effectiveness of the BOPPPS strategy compared with traditional lecture-based learning (LBL) in Chinese medical education. The English electronic databases of Web of Science, PubMed, Embase, and the Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…The BOPPPS teaching model was introduced to our teaching reform in order to stimulate interns' learning initiative and bring teachers' guidance into full play. The BOPPPS was rst proposed by the teaching skills training institutions of universities in North America [5], which emphasizes intern-centered, all-round participation and interactive feedback between teachers and interns. Meanwhile we integrate the BOPPPS with online teaching platform to promote the utilization of teaching resources and the development of teaching interaction, and also enable interns to better participate in the whole process of learning activities, and improve the enthusiasm and initiative of learning [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The BOPPPS teaching model was introduced to our teaching reform in order to stimulate interns' learning initiative and bring teachers' guidance into full play. The BOPPPS was rst proposed by the teaching skills training institutions of universities in North America [5], which emphasizes intern-centered, all-round participation and interactive feedback between teachers and interns. Meanwhile we integrate the BOPPPS with online teaching platform to promote the utilization of teaching resources and the development of teaching interaction, and also enable interns to better participate in the whole process of learning activities, and improve the enthusiasm and initiative of learning [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The CBL design adopts real clinical cases to restore real clinical scenarios. Real cases and scenarios are bene cial in encouraging students to apply theoretical knowledge to case analysis [10], developing students' problem-solving ability [4], and facilitating team assistance [10]. The BOPPPS design emphasizes students' active participatory learning and has obvious advantages over traditional teaching in improving learning initiative, analytical ability, clinical thinking ability, and self-study ability [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…This model divides the teaching process into six elements: bridge-in (B), objective (O), pre-assessment (P), participatory learning (P), post-assessment (P), and summary (S) [9]. The model follows the educational concept of "student-oriented, teacher-led", and emphasizes students' participatory learning in the course [10]. In recent years, the BOPPPS model has been widely applied by educational institutions and universities in China and gradually applied in medical education, such as thoracic surgery, and dental materials education [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…SBE is a rapidly developing medical strategy, which supplements and enhances clinical education, especially the clinical skills scores of medical students 17 25 26. A previous meta-analysis revealed that BOPPPS contributed to increase knowledge examination scores, skill scores and satisfaction of medical students compared with the LBL 18…”
Section: Introductionmentioning
confidence: 99%